2008
DOI: 10.1017/s0265051708008127
|View full text |Cite
|
Sign up to set email alerts
|

From music student to professional: the process of transition

Abstract: This article addresses the question of whether higher education music courses adequately prepare young musicians for the critical transition from music undergraduate to professional. Thematic analyses of interviews with 27 undergraduate and portfolio career musicians representing four musical genres were compared. The evidence suggests that the process of transition into professional life for musicians across the four focus genres may be facilitated when higher education experiences include mentoring that cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
86
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(90 citation statements)
references
References 13 publications
1
86
0
3
Order By: Relevance
“…For example, in Bennett's survey of performing arts, the most common response provided by student on the changes that they would make to their education and training included, 'open discussion about the realities of working life and the limited performance opportunities ' (2009, 320). The realities of working life as posed here connect with the reference to 'real and imagined challenges' by Creech et al (2008) and the coping strategies noted by Ball, Pollard, and Stanley (2010). Engaging students with issues of unstable employment conditions is not a case of 'smashing childlike wonder' (Noonan 2013).…”
Section: Workforce Expectationsmentioning
confidence: 64%
See 2 more Smart Citations
“…For example, in Bennett's survey of performing arts, the most common response provided by student on the changes that they would make to their education and training included, 'open discussion about the realities of working life and the limited performance opportunities ' (2009, 320). The realities of working life as posed here connect with the reference to 'real and imagined challenges' by Creech et al (2008) and the coping strategies noted by Ball, Pollard, and Stanley (2010). Engaging students with issues of unstable employment conditions is not a case of 'smashing childlike wonder' (Noonan 2013).…”
Section: Workforce Expectationsmentioning
confidence: 64%
“…In their discussion of the steps that a music student makes in becoming 'professional', Creech et al (2008) describe transition as a process, rather than an event. They go on to consider how the process of transition, 'opens up a space in the imagination where the individual has the capacity to anticipate future possibilities in relation to present action and to begin to develop effective coping strategies for dealing with real or imagined challenges lying ahead' (Creech et al 2008, 316).…”
Section: Part Four: Students From Creative Courses In Non-creative Ocmentioning
confidence: 99%
See 1 more Smart Citation
“…(82) All musicians are vying for a place in the professional world; however, scholars in this field argue that the skills and knowledge required for success are now much broader. Creech et al (2008) conducted in-depth interviews with twenty-seven classical musicians who were in the early stages of their professional careers in the United Kingdom. They found that the competitive nature of the industry presented several challenges for newcomers to the music profession.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Their musical skills need to be as refined as ever. In addition, they need to develop flexibility and entrepreneurialism, personal confidence, communication skills and artistic imagination (Creech et al 2008). They also need to be much more acutely aware of their abilities and passions and adept at finding ways to apply these within the workplace.…”
Section: The Changing Professional Context For Musiciansmentioning
confidence: 99%